STUDI PENERAPAN HACCP PADA PROSES PRODUKSI SARI BUAH APEL - Widaningrum Widaningrum; Christina Winarti (JURNAL STANDARDISASI, 2007)
Of one among agriculture postharvest processing agroindustries in Indonesia is fruit juice agroindustry. Nowadays beverage industry in Indonesia has growth in a large number. Particular factor which support it is ingredients readiness especially many kinds of fruits, one among them are apple. The aim of this study is to assess the Hazard Analysis Critical Control Points (HACCP) system guidelines which is suitable for apple juice processing on small-medium enterprise scale in order to fulfill the requirement on Indonesian National Standard (SNI)for fruit juice. The arranging of HACCP plan is based on 7 principles and 12 steps of HACCP system guidelines. From HACCP study on raw materials of apple juice, has come 2 (two) materials being CCP, they are apple fruit and water. On apple juice processing, there are 5 (five) stages of process being CCP, they are grading, washing, straining to separate liquid from solid, boiling and packaging, meanwhile there are 3 (three) stages being CCP i.e. cutting of apple fruit manually (using knife), boiling (to get apple juice extract) and mixing the ingredients (sugar, caramel coloring and preservation). On this study, HACCP application has been succeeded due to its ability to reduce amount of total microbes either on every stage of apple juice processing or in its product. Production process had also fulfilled the requirements on SNI 01-3719-1995 for fruit juice which required that the product must contain maximum 2x102 colony/ml for total microbes, 50 colony/ml for molds, 50 colony/ml for yeast and < 3 APM/ml for E.coli. Therefore, applying HACCP system in apple juice processing is quite necessary to improve its quality and guarantee the safety of apple juice especially for direct consumption. HACCP application should be audited minimum every 4 (four) month by officially local Agriculture Government.